Correlates and Predictors of Sexual Health among Adolescent Latinas in the United States: A Systematic Review of the Literature, 2004-2015 - Morales-Alemán, Mercedes M. (Prev Med, 2016)
Adolescent Latinas in the United States (US) are disproportionately affected by early pregnancy, sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) in comparison to their non-Hispanic white counterparts. However, only a few studies have sought to understand the multi-level factors associated with sexual health in adolescent Latinas. Adhering to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, we conducted a systematic literature review to better understand the correlates and predictors of sexual health among adolescent Latinas in the US, identify gaps in the research, and suggest future directions for empirical studies and intervention efforts. Eleven studies were identified: five examined onset of sexual intercourse, nine examined determinants of sexual health/risk behaviors (e.g., number of sexual partners, condom use etc.), and three examined determinants of a biological sexual health outcome (i.e., STIs or pregnancy). Two types of variables/factors emerged as important influences on sexual health outcomes: proximal context-level variables (i.e., variables pertaining to the individual's family, sexual/romantic partner or peer group) and individual-level variables (i.e., characteristics of the individual). A majority of the studies reviewed (n=9) examined some aspect of acculturation or Latino/a cultural values in relation to sexual health. Results varied widely between studies suggesting that the relationship between individual and proximal contextual variables (including acculturation) and sexual health may be more complex than previously conceived. This review integrates the findings on correlates and predictors of sexual health among adolescent Latinas, and supports the need for strengths-based theoretically guided research on the mechanisms driving these associations.